ANALISIS KONTEKS SITUASI DALAM PUTUSAN KASASI - Sugiharyanti, Eni (Adabiyyāt: Jurnal Bahasa dan Sastra, 2019)
One of the specialized varieties of language which is known in human communication is the language of law. This variety of language can be found in some documents such as regulations, bills, and court’s decree. A decree uses special register whose existence is influenced by the context of situation, i.e. the field of discourse, the tenor, and the mode. These three dimensions of the context of situation in a decree released by the Supreme Court are the objects of this research. Conducting research on the context of situation of a text is important because by understanding the context we can understand the whole meaning of a text. The researcher used qualitative research methods to reveal the context of situation of the text of this legal language variety. The primary data are derived from the Supreme Court’s decree Number 210 K/Ag/ 2014, and they are analyzed using Systemic Functional Linguistics theory by Halliday and Eggins to answer the research problems. The research found that the context of the situation consisting of field, tenor and mode plays an important role in the realization of the text. These three dimensions are interrelated to build a discourse of a text.